Basis and foundation in the process and result of educational research - Aguirre Chávez, Felipe (2017)
In social historical development, the base and foundation categories make up two different issues, but in turn, intrinsically connected. There is no object, field or social dimension beyond its reach. Perhaps, metaphorically speaking, base and foundation make up the seal and face of the same coin. The variables, categories, concepts, definitions, assumptions, judgments, reasoning and arguments are determined by their bases and foundations. In this article we intend to answer the questions What do we call base? And what do we call foundation? Two essential issues important for educational scientific research.